Knockdown of STIM1 expression inhibits non-small-cell lung cancer cell proliferation in vitro and in nude mouse xenografts. Issue 1 (1st January 2019) - Ge, Chunlei; Zeng, Baozhen; Li, Ruilei; Li, Zhen; Fu, Qiaofen; Wang, Weiwei; Wang, Zhenyu; Dong, Suwei; Lai, Zhangchao; Wang, Ying; Xue, Yuanbo; Guo, Jiyin; et al.
ABSTRACT: Stromal interaction molecule 1 (STIM1) is a calcium-sensing protein localized in the membrane of the endoplasmic reticulum. The expression of STIM1 has been shown to be closely associated with cell proliferation. The aim of the present study was to investigate the role of STIM1 in the regulation of cancer progression and its clinical relevance. The data demonstrated that the expression of the STIM1 was significantly higher in non-small-cell lung cancer (NSCLC) tissues than in benign lesions and was associated with advanced NSCLC T stage. Knockdown of STIM1 expression in NSCLC cell lines A549 and SK-MES-1 significantly inhibited cell proliferation and induces A549 and SK-MES-1 cell arrest at the G2/M and S phases of the cell cycle. Western blotting showed that the expression of cyclin-dependent kinase (CDK) 1 and CDK2 were reduced while knockdown of STIM1 expression. Furthermore, knockdown of STIM1 in NSCLC cells significantly reduced the levels of xenograft tumor growth in nude mice. These data indicate that aberrant expression of the STIM1 protein may contribute to NSCLC progression. Future studies should focus on targeting STIM1 as a novel strategy for NSCLC therapy.